Assessing the risk of climate maladaptation for Canadian polar bears - L. Ruth Rivkin; Evan S. Richardson; Joshua M. Miller; Todd C. Atwood; Steven Baryluk; Erik W. Born; Corey Davis; Markus Dyck; Evelien de Greef; Kristin L. Laidre; Nicholas J. Lunn; Sara McCarthy; et al. (Ecology Letters, 2024)
The Arctic is warming four times faster than the rest of the world, threatening the persistence of many Arctic species. It is uncertain if Arctic wildlife will have sufficient time to adapt to such rapidly warming environments. We used genetic forecasting to measure the risk of maladaptation to warming temperatures and sea ice loss in polar bears ( Ursus maritimus ) sampled across the Canadian Arctic. We found evidence for local adaptation to sea ice conditions and temperature. Forecasting of genome‐environment mismatches for predicted climate scenarios suggested that polar bears in the Canadian high Arctic had the greatest risk of becoming maladapted to climate warming. While Canadian high Arctic bears may be the most likely to become maladapted, all polar bears face potentially negative outcomes to climate change. Given the importance of the sea ice habitat to polar bears, we expect that maladaptation to future warming is already widespread across Canada.